Improving lives together in Bangladesh 50 years of the Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2017)
This report highlights the milestones in the Bangladesh ADB partnership since 1973, including projects that exemplify sustained development results.
Keywords: Joint ventures -- Bangladesh; Investments, Foreign -- Bangladesh; Economic development -- Asian Development Bank -- China; Electronic books